Remote Intelligent Tutoring System Based on Multi-Agent - Yi Zhenzhen; Zhao Ke; Li Yatao; Cheng Peitao (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
This paper describes a system named Remote Intelligent Tutoring System (RITS) provides students an environment on internet. In this system, students can learn abundant knowledge of one or many subjects, conveniently input problem, and acquire real-time feedback with multiple tutorship information as an excellent teacher do. It synthetically adopts multi-agent technology for overall system modeling, knowledge-based technology for automatic solving problem and network technology for remote communication, database technology for students' information analysis. Besides, the system takes education rules into account to enhance study interest and efficiency. The system can serve as not only a learning and tutoring tool to the students but also an assistant to teachers inquiring relative material.